Art and work of the primitive men in the Altiplano. Description of the pictographic manifestations of Oqhoruni in the community of Isivilla in Puno (Revista revoluciones, 2021)
From a qualitative study model, observation and documentary analysis, the aim is to describe the iconographic figures of the pictographic manifestations of Oqhoruni in the Isivilla community of the Corani-Carabaya district in Puno. The results show that the description of said pictographic expressions from some scenes such as anthropomorphic, zoomorphic and geometric figures, mostly highlight strong hunting scenes, the chaco and the caicu. In that odd one, it especially draws the attention of geometric figures, vertical parallel lines and painted in colors of dark red, orange, yellow and white. Within these manifestations, it can be concluded that there is no doubt that the art and work of primitive men in the highlands have not only reflected and left on the rocky surfaces real activities that surrounded them in the environment where they lived thousands of years ago . But in addition, a strong insistence to be immortalized in the enchantments of Oqhoruni is seen in the distance.
Keywords: Community; description; historical Isivilla; pictographic manifestation